METHODOLOGICAL BASES OF BLENDED LEARNING IN THE HIGHER EDUCATION - Olga Korotun (Kherson State University, 2016)
State policy of Ukraine in higher education, accordance with the Act "On education» (№ 1556-VII) aimed at ensuring the availability, quality and effectiveness of education. There are different solutions, one of which is education informatization. In turn informatization can effectively develop pedagogical technology as blended learning. The actual problem is the use of blended learning technologies in modern Ukrainian university. The article is devoted to methodological bases of the educational process in the higher education with the use of educational technology blended learning. In the work analyzed and refined the concept of "blended learning", identified methodological approaches, a number of common didactic and methodological principles that underpin the process of learning in higher education with the use of blended learning models. The described methods and forms of organizing and tools used in the mixed teaching and advantages of this learning model. The article is developed model of blended learning in a higher education.